Mirror mode structures ahead of dipolarization front near the neutral sheet observed by Cluster - G. Q. Wang; T. L. Zhang; M. Volwerk; D. Schmid; W. Baumjohann; R. Nakamura; Z. H. Pan (Geophysical Research Letters)
Abstract Magnetic compressional structures ahead of a dipolarization front (DF) on 30 August 2002 are investigated by using Cluster data. Our findings are as follows: (1) the structures, observed near the neutral sheet, are mainly compressional and dominant in BZ; (2) they are almost nonpropagating relative to the local ion bulk flow and their lengths are several local proton gyroradius; (3) the ion density increases when BT decreases; (4) ions are partially trapped by the structures with parallel and perpendicular velocities varying in antiphase; and (5) local conditions are favorable for excitation of the mirror instability, and we suggest that these structures are mirror mode‐like. Our findings also suggest that local conditions ahead of the DF are viable for exciting the mirror instability to generate mirror mode waves or structures.